EFEKTIVITAS KOMPRES JAHE TERHADAP PENURUNAN SKALA NYERI SENDI PENDERITA ASAM URAT DI DESA TEMPUREJO DAN JURUG JUMAPOLO KARANGANYAR - Lilik Sriwiyati; Dwi Noviyanti (KOSALA : Jurnal Ilmu Kesehatan, 2018)
Background : The uric acid disease continues to increase in prevalence, with the mainsymptom being severe pain in the joints. One of the non-pharmacological painmanagement is to use warm compresses, one of which the ingredients can use gingerbecause ginger contains some substances that can reduce pain. The purpose of thisstudy was to analyze the effectiveness of ginger compress on decreasing the scale ofjoint pain in people with uric acid in Tempurejo dan Jurug JumapoloSubjects of this research : were Tempurejo and Jurug villagers. The samples were 22respondents selected by using total sampling method. Method of the research is aqueasy experiment with pre-post test design. This research has two variables, theindependent variable is compressed ginger and the dependent variable is pain scale.Collecting data use observation paper. Data analysis using paired t-test with p=0.05The result of this research : is the average scale of the pain before giving the gingercompress is 4.18 with standard deviation Â± 1.053. While the average scale of pain afterthe ginger compression is done 2.73 with standard deviation + 1.162. The meandifference of pain scale before and after giving ginger compress is 1.455 with standarddeviation + 0.671. The p-value is 0.000.The Conclusion of this research : is a ginger compress effective against the decrease inpain scale of uric acid sufferers on villagers of Tempurejo and Jurug Jumapolo.Keywords: stress level, menstrual cycles